Loricate Ciliate Tintinnids in a Tropical Mangrove Wetland Diversity, Distribution and Impact of Climate Change - Sarkar, Santosh Kumar (SpringerBriefs in Environmental Science, 2015)
This book is an integrated approach to present a detailed case study in order to address the taxonomic and ecological features of this planktonic choreotrich protists in an iconic tropical mangrove wetland - Sundarban. To identify each tintinnid species, emphasis is given with regards to taxonomic features accompanied by high resolution images. This work explores the interaction between man-induced stress and the  impact of climate change which is threatening the tintinnid biodiversity, and suggests, for example, remedial measures by adopting sound management strategies. Tintinnids  (Protozoa: Ciliata: Tintinnida) are a coherent group ecologically recognized as micro-zooplankton. They deserve  special attention because of their  unique biodiversity and  their  crucial, functional role in the marine food chain. This is a valuable reference source for students, researchers, policy planners and coastal managers engaged in the field of marine biology, microbial ecology and  marine bio-resources.